2014
DOI: 10.24925/turjaf.v3i1.40-44.166
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Antioxidant Properties of Wild Blueberries (Vaccinium arctostaphylos L. and Vaccinium myrtillus L.) with Cultivated Blueberry Varieties (Vaccinium corymbosum L.) in Artvin Region of Turkey

Abstract: Vaccinium arctostaphylos L. and Vaccinium myrtillus L. which are found naturally in most part of Blacksea Region, and Artvin are generally called bear grape, Trabzon tea, and likapa. In addition, different varieties of blueberry (Vaccinium corymbosum L.) have been cultivated in Artvin region for 5 or 6 years. Blueberries contain appreciable levels of phenolic compounds, including anthocyanins and flavonols that have high biological activity. V. arctostaphylos and V. myrtillus show that natural distrubition wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 18 publications
4
20
0
Order By: Relevance
“…In this study, EE had the highest total anthocyanin content with 8.46 ± 0.49 mg CGE/g dry weight among extracts tested. Similar to our findings, Saral reported that ME of V. arctostaphylos was 6.14 ± 0.01 mg CGE/g dry weight (36). The results obtained in this study demonstrated that V. arctostaphylos is rich source of secondary metabolites.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In this study, EE had the highest total anthocyanin content with 8.46 ± 0.49 mg CGE/g dry weight among extracts tested. Similar to our findings, Saral reported that ME of V. arctostaphylos was 6.14 ± 0.01 mg CGE/g dry weight (36). The results obtained in this study demonstrated that V. arctostaphylos is rich source of secondary metabolites.…”
Section: Discussionsupporting
confidence: 81%
“…arctostaphylos fruits from different regions were found to range from 20.74 ± 0.24 mg GAE/ g weight of samples (36). Hasanloo reported that acidic ME of the plants was found to contain 9.48 mg GAE/g dry weight.…”
Section: Discussionmentioning
confidence: 99%
“…Also, they are very effective during the storage and transport of oils and fats, but they are less effective at frying temperatures, due to their volatility. However, in the recent years, much of the interest has developed in naturally occurring antioxidants, because of the adverse attention received by the synthetic antioxidants, and because of the worldwide trend to avoid or minimize the use of artificial food additives (Filiz and Seydim, 2014;Gad and Sayd, 2015;Saral et al, 2014). Also the use of natural antioxidants for frying purposes has increased during the last few years (Bera et al, 2006;Budak et al, 2015;Riveros et al, 2015;Urbancic et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The anthocyanins are found mainly in skin and pulp of the bilberry fruit (Akerstrom, 2010;Oancea et al, 2013;Saral et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The bilberry contains anthocyanin which is considered to be an important natural antioxidant (Prior et al, 1998;Huang et al, 2012;Saral et al, 2015;Zoratti et al, 2016). Anthocyanins are the colorant/pigment of the fruit and flowers (Chandra et al, 2001;Fe et al, 2010;Huang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%